Fluidized Bed Steam Generators for Direct Particle Absorption CSP-plants. (May 2015) - Schwaiger, K.; Haider, M.; Haemmerle, M.; Steiner, P.; Walter, H.; Obermaier, M.
Abstract: For direct particle absorption CSP-plants heat exchanger between particles and the working fluid of the power cycle are needed. A fluidized-bed heat-exchanger design operating close to the minimum fluidization condition is proposed in this work. Its basic design and core components are explained.For illustrating the performance of this fluidized-bed heat-exchanger its application as evaporator and superheater in sub- and supercritical cycle are presented. Therefore overall design parameters of all heat exchangers and a detailed process flow diagram including all major componentsare shown. The particle mean diameter is varied to illustrate its significance to auxiliary power consumption.